Do juiz de paz : análise da instituição no Estado do Espírito Santo sob a luz do acesso à justiça - Barcelos, Débora Ceciliotti (2013)
This paper undertakes an analysis of the process of establishment of the Justice of the Peace in Brazil from the 1988 Federal Constitution attempting to understand, ultimately, their political, social and legal, against the attempt to regulate that function in Espírito Ghost. Therefore, fulfilled Achieving democratic understanding and implications of the judicial system in the context of recent access to justice. The analysis of the Portuguese justice of peace, in which it sought to understand the role of the institute in question in the legal reaffirmed certain assumptions intrinsic to the condition that the misfit Justice of the Peace engenders in its relationship with the magistrate and legal implications of their activity distinct celebrate weddings and resolve conflicts within the alternative methods of conflict resolution. It follows from this relation the inconsistencies present in the legislation that aims to introduce it in the States of the Federation, particularly for this work, in Espírito Santo. Legal instruments such as the injunction and the construction of new paradigms for teaching and practice of law is binding in this context as measures to bring the desired effect for the function of regulatory Justice of the Peace in Brazil.